Ultrasonographic findings of thyroglossal duct papillary carcinoma: A case report. (2017) - Srivanitchapoom, Chonticha; Sittitrai, Pichit; Yata, Kedsaraporn; Khongpiboonkit, Piyadara
Highlights: Thyroglossal duct cyst carcinoma can be classified as primary, secondary and multicentric. Preoperative ultrasound with possible fine needle aspiration biopsy are useful for determining the extent of the operation. The treatment is Sistrunk's operation with the addition of total thyroidectomy and neck dissection when indicated. Abstract: Introduction: Reports on thyroglossal duct cyst carcinoma (TGDCCa) are rare, occurring in approximately 1% of thyroglossal duct cyst (TGDC) cases. The origin and treatment of carcinoma arising in TGDC are controversy. Presentation of case: A 38-year-old woman presented with a midline neck mass at the thyrohyoid level for 3 years. Ultrasound revealed a 2.4 cm cystic mass with a solid mural component and microcalcification. A small right thyroid nodule was also detected. Sistrunk's operation was performed and the pathology was a primary carcinoma arising in the TGDC with a close surgical margin. Total thyroidectomy was done and revealed a 4 mm papillary carcinoma with partial invasion through the thyroid capsule of the right lobe with a 1 mm papillary carcinoma at the isthmus. The diagnosis was a primary TGDCCa with multifocal papillary thyroid carcinoma. Discussion: Sistrunk's operation is an accepted procedure for the treatment of both TGDC and TGDCCa. Additional total thyroidectomy has been proposed but still controversial. The aims of preoperative ultrasound and ultrasound-guided fine needle aspiration biopsy (FNAB) are differential diagnosis of the possible diseases and operative planning. The results which suggest a carcinoma arising in the TGDC, synchronous thyroid malignancy and metastatic cervical lymph nodes are helpful in determining the magnitude of the operation. Conclusion: Ultrasound and FNAB of the TGDC, thyroid gland and cervical lymph nodes are the useful preoperative evaluations leading to the accurate diagnosis. The definitive treatment is Sistrunk's operation with the possible addition of total thyroidectomy and neck dissection when indicated.